2015
DOI: 10.1016/j.ecoenv.2015.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Contamination and risk of heavy metals in soils and sediments from a typical plastic waste recycling area in North China

Abstract: a b s t r a c tPlastic wastes are increasingly being recycled in many countries. However, available information on the metals released into the environment during recycling processes is rare. In this study, the contamination features and risks of eight heavy metals in soils and sediments were investigated in Wen'an, a typical plastic recycling area in North China. The surface soils and sediments have suffered from moderate to high metal pollution and in particular, high Cd and Hg pollution. The mean concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(63 citation statements)
references
References 42 publications
0
58
0
3
Order By: Relevance
“…Compared to China' other MAs, smelting sites and the e-waste dismantling area, the HM concentrations in soil of our study areas were much lower (Li et al , 2015Wei et al 2009;Yan et al 2015). However, the HM concentrations in soil of our study areas were comparable to those of a plastic waste recycling area with moderate to high metal pollution (Tang et al 2015), and obviously higher than those observed from the contaminated urban areas in China (Cheng et al 2014). Thus, the studied areas were suffering from moderate to high HM pollution.…”
Section: Concentrations Of Heavy Metalsmentioning
confidence: 62%
“…Compared to China' other MAs, smelting sites and the e-waste dismantling area, the HM concentrations in soil of our study areas were much lower (Li et al , 2015Wei et al 2009;Yan et al 2015). However, the HM concentrations in soil of our study areas were comparable to those of a plastic waste recycling area with moderate to high metal pollution (Tang et al 2015), and obviously higher than those observed from the contaminated urban areas in China (Cheng et al 2014). Thus, the studied areas were suffering from moderate to high HM pollution.…”
Section: Concentrations Of Heavy Metalsmentioning
confidence: 62%
“…For instance, among the studied heavy metals, namely, As, Cd, Cr, Cu, Hg, Pb, Sb, and Zn, in soils from Wen'an County, Hebei Province in China, the potential ecological risks caused by Cd and Hg was found to be highest, which posed considerable and dangerous potential eco-risk (E(Cd) 125; E(Hg) 523), respectively (Tang et al 2015). In the soil from other megacities such as Beijing and Shenzhen, cadmium and Hg were also observed to be much higher than other studied heavy metals with respect to potential ecological risk.…”
Section: Potential Ecological Risk Assessmentmentioning
confidence: 99%
“…The table was elaborated from National Institute of Ecology and Climate Change (INECC by its acronym in Spanish) studies [19][20][21][22][23][24] and with interviews and field visits to 27 recycling e-waste companies in Mexico [25]. The WEEE contain heavy metals such as lead (Pb), cadmium (Cd), chromium (Cr), manganese (Mn), nickel (Ni), mercury (Hg), arsenic (As), copper (Cu), zinc (Zn), aluminum (Al) and cobalt (Co) [27,28] and organic pollutants, including polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs), brominated flame retardants (BFRs), such as polybrominated diphenyl ethers (PBDEs), or other compounds such as polychlorinated dibenzo-p-dioxin/furans (PCDD/Fs) [29], which can be released from artisanal thermal recycling processes or inadequate recycling processes of WEEE [30], and subsequently have been found in different environmental matrices with adverse negative environmental effects [31,32].…”
Section: Electronic Waste In the Waste Stream System In Mexicomentioning
confidence: 99%